5-Flouorouracil Is an Attractive Medical Treatment in Women With Vaginal Intraepithelial Neoplasia: A Meta-Analysis. Issue 4 (October 2018) - Tranoulis, Anastasios; Georgiou, Dimitra; Laios, Alexandros; Theophilou, Georgios; Thangavelu, Amudha; Hutson, Richard Chanellor
Abstract : Objective: In the absence of standard guidelines, the management of vaginal intraepithelial neoplasia (VaIN) remains a field of debate. The aim of this systematic review and meta-analysis was to ascertain the 5-flouorouracil (5-FU) effectiveness in this context. Materials and Methods: A literature search was conducted throughout the PubMed, EMBASE, SCOPUS, ClinicalTrials.gov, and Cochrane Databases for relevant studies. We computed the summary proportions of women treated for VaIN with 5-FU for the outcomes of complete response and recurrence by random-effects meta-analysis. We also performed a subgroup analysis by computing the summary proportions for complete response among women with high-grade VaIN, persistent disease, and recurrence respectively. Results: Fourteen observational studies reporting on 358 women included in the study. The study quality was moderate. The summary proportions of women who had complete response after the first 5-FU course were 82.18% (95% CI = 69.80%–88.82%). The summary proportions of women who recurred were 16.42% (95% CI = 7.39%–28.14%). The summary proportions of women with complete response in the high-grade VaIN, persistent disease, and recurrence subgroups were 77.53% (95% CI = 59.90%–91.15%), 53.92% (95% CI = 34.62%–72.61%), and 72.32% (95% CI = 48.12%–91.05%), respectively. Conclusions: This is the first meta-analysis to date to provide a convincing overview of 5-FU efficacy on the VaIN treatment. Albeit a medium risk of bias warrants some caution with interpretation of the results, 5-FU can be an attractive alternative to surgery, especially among young women with multifocal and recurrent disease. Abstract : Supplemental digital content is available in the text.